2010
DOI: 10.1524/ract.2010.1757
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Tc(IV) with acetate at varying ionic strengths

Abstract: In order to accurately model and predict the fate and transport of metals and radionuclides at multiple radio-contaminated sites, there is a need for an understanding on how metals such as technetium interact with their environment. Many contaminated sites are known to contain large amounts of organic ligands that can affect the solubility and mobility of metals. This study focuses on the effect of acetate on the complexation and dissolution of Tc(IV). Studies were performed at pcH 4.5 (±0.3), at which TcOOH +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
4
35
0
Order By: Relevance
“…gluconate, EDTA). This explanation for the increase in solubility agrees with published complexation studies, as Tc(IV) was shown to form soluble complexes with oxalic acid [15], acetate [16], and humic substances [17].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…gluconate, EDTA). This explanation for the increase in solubility agrees with published complexation studies, as Tc(IV) was shown to form soluble complexes with oxalic acid [15], acetate [16], and humic substances [17].…”
Section: Introductionsupporting
confidence: 91%
“…Tc(IV) stock solution was prepared according to Hess et al [22] and Boggs et al [16] using a 0.29 M NH 4 TcO 4 (Oak Ridge). The resulting Tc(IV) precipitate was dissolved in concentrated HCl (Fisher) and aliquots were used to prepare a working solution of ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of strong organic complexants, the product of Tc(VII) reduction in anaerobic, alkaline, aqueous solution is hydrous Tc(IV) dioxide, TcO 2 -xH 2 O. The solubility of the hydrous Tc(IV) dioxide produced by alkaline pertechnetate reduction has been studied both in simple aqueous solutions and in the presence of various organic ligands (Boggs et al 2010;Gu et al 2011;Warwick et al 2007;Xia et al 2006). Based on this work, it appears unlikely that in the absence of strongly chelating organic ligands, soluble Tc(IV) compounds can account for the concentrations of n-Tc observed in several Hanford tanks.…”
Section: Sy 103mentioning
confidence: 99%